1989
DOI: 10.1002/clc.4960120408
|View full text |Cite
|
Sign up to set email alerts
|

Long QT syndrome associated with inflammatory degeneration of the stel ganglia

Abstract: Summary:A well-studied case of intermittent long QT syndrome in a 21 -year-old female is presented. Electrophysiologic investigation repeated three times revealed changing sinoatrial and atrioventricular dysfunction and nonsustained ventricular tachycardia. The patient died 29 months after first hospitalization in a stage of electromechanical dissociation after runs of torsade de pointes although she had been treated with repeated anti-inflammatory therapy as well as high doses of propranolol. Postmortem exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…On the basis of these findings, the authors speculated that a T-cell-mediated cytotoxicity toward ganglion cells may boost adrenergic activity through release of inflammatory mediators in ganglia and in this manner contribute to the electric instability in LQTS/CPVT patients, particularly in those who are heavily symptomatic. In accordance with this view, intracardiac ganglionitis and its pro-arrythmic potential have been previously described in LQTS patients who died suddenly, the first time over 35 years ago ( 163 165 ). Moreover, although the origin of inflammatory infiltrates remains unknown, Rizzo et al ( 162 ) put forward the hypothesis of a viral (however not herpes-virus DNA was found in specimens) or autoimmune pathogenesis.…”
Section: Do Inflammation and Immunity Play A Role In Congenital Lqts?supporting
confidence: 64%
“…On the basis of these findings, the authors speculated that a T-cell-mediated cytotoxicity toward ganglion cells may boost adrenergic activity through release of inflammatory mediators in ganglia and in this manner contribute to the electric instability in LQTS/CPVT patients, particularly in those who are heavily symptomatic. In accordance with this view, intracardiac ganglionitis and its pro-arrythmic potential have been previously described in LQTS patients who died suddenly, the first time over 35 years ago ( 163 165 ). Moreover, although the origin of inflammatory infiltrates remains unknown, Rizzo et al ( 162 ) put forward the hypothesis of a viral (however not herpes-virus DNA was found in specimens) or autoimmune pathogenesis.…”
Section: Do Inflammation and Immunity Play A Role In Congenital Lqts?supporting
confidence: 64%
“…Normal ganglia also Intracardiac ganglionitis and its potential effect on arrhythmic risk have been previously described in LQTS subjects who died suddendly. [25][26][27] Ganglionitis and neuritis in the sinus node area were found also in liquid-protein-modified fast diet dieters who developed prolongation of the QT interval and ventricular arrhythmias after dieting. 28 In these studies, diffuse infiltration of mononuclear cells associated with neural degeneration was found at histological examination, lacking however of an immune characterization of the cellular composition and activity of the inflammatory population.…”
Section: Discussionmentioning
confidence: 97%
“…The term 'ganglionitis' was used to describe this phenomenon, and its associated malignant cardiac rhythm. A decade later, Pfeiffer et al (1989) described the first case of a young patient with a structurally normal heart, but with severe inflammation of the SG, linking viral-mediated neuronal dysfunction in SGs to malignant arrhythmogenesis in this patient. Recently, in patients with congenital long QT syndrome (LQTS) and catecholaminergic polymorphic ventricular tachycardia (CPVT), Rizzo et al (2014) observed evidence of T cell-mediated inflammation.…”
Section: Extra-cardiac Neuronalmentioning
confidence: 99%